Factors constituting mall culture and mall shopping experience: An Empirical Study - Sanjay Negi, Unmesh Mandloi; Shubha R Singh (International Journal of Advanced Science and Technology, 2020)
The recent exploration deals in determining the factors that boost the shopping mall culture. The contemporary world values time more than anything else. With the advent of technology and growing means of transforming tools of entertainment, people have started wanting extra. The increasing income capability has augmented the need for sophistication and opulence. The idea of amusement, shopping, gaming, eating under one roof was expected to be a successful project. Therefore, the amalgamation of stores in a single building attracted people and helped in enhancing the trend and laying slabs of modernization. The sample size of the study is 145 which have been taken from participants through structure questionnaire designed on five point interval scale.